The Influence of Work Culture and Work Environment on Employee Work Motivation with Leadership as Moderating Variables at Representative Offices the Bank Indonesia Representative Offices of North Sumatra Province - Widya Susanti; Husni Muharram (CV. Doki Course and Training, 2026)
This study aims to examine the influence of work culture and work environment on employee work motivation with leadership as a moderating variable at the Representative Office of Bank Indonesia in North Sumatra Province. A quantitative approach was employed, and data were collected through questionnaires distributed to employees. The data were analyzed using Partial Least Square (PLS). The results reveal that both work culture and work environment have a positive and significant effect on employee work motivation. Furthermore, leadership positively moderates the relationship between work culture and motivation but negatively moderates the relationship between work environment and motivation. These findings indicate that a strong work culture and a supportive work environment can enhance motivation, while the effectiveness of leadership plays a crucial role in strengthening or weakening these relationships. This research is expected to contribute theoretically and practically to the development of human resource management within banking institutions, particularly Bank Indonesia.